Efficient Direct and Modular Stereoselective Synthesis of Highly Functionalized Tetrahydroisoquinolines and C2-1,1′-Bitetrahydroisoquinolines - Thinh, Khong Duc; Judeh, Zaher M. A. (Synthesis, 2014)
An efficient modular stereoselective synthesis of highly functionalized tetrahydroisoquinolines and C2-1,1′-bitetrahydroisoquinolines chiral ligands is disclosed. The synthetic methodology relies on direct stereoselective Pictet–Spengler cyclization between (S)-4-benzyloxazolidin-2-ones and various mono- and dialdehydes using inexpensive sulfuric acid as the catalyst.
Keywords: stereoselective synthesis; chiral bitetrahydroisoquinolines; C2-symmetric chiral ligands; diastereoselective Pictet–Spengler reaction; isoquinoline